Potential Economic Impacts of the Vietnam-Korea Free Trade Agreement on Vietnam - Thanh Hoan Phan; Ji Young Jeong (East Asian Economic Review, 2016)
This paper provides an assessment of the potential economic impacts of the Vietnam-Korea free trade agreement on Vietnam, by using general equilibrium modeling. The results show that Vietnam-Korea FTA will increase aggregate welfare for both countries in the long run. The most important gains accrue from better allocation of resources consequent to trade liberalization. All the sectoral differences and changes are consistent with the trade profiles of the two countries, and the long-run results are more pronounced than those of the short-run. In comparison with other ASEAN countries, the CGE analysis suggests that Vietnam's agriculture exports to Korea would especially rise in the long run. However, there will be strong competition in this sector among ASEAN members. Thus, an earlier conclusion of a comprehensive FTA with Korea is expected to be a good strategy for Vietnam, so as to avoid the direct competition with ASEAN members in the future.